Merefleksikan ibadah nabi-nabi abad delapan dalam ibadah new normal - Susila, Tirta (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
This study examines the prophet Amos' perspective on worship and its implications in new normal worship. Researchers use qualitative methods with literature studies to obtain the purpose of the research. The results revealed that: first, worship should avoid excitement, luxury, and hypocrisy. The church and the people of God today need to avoid worship that highlights the excitement and luxury that can distance itself from God, instead prioritizing social care and simple worship pleasing to God's eyes. Second, worship should be accompanied by an attitude that is faithful to God and away from sinful acts. With loyalty, any condition, including the new normal today does not prevent a person from doing personal worship or worship together, and dedication does not make oneself far from the place of worship. Third, worship should be accompanied by justice, truth, and holiness. Worship is accompanied by actual acts of justice and fact in social interaction. Fourth, worship should be accompanied by sacrifices and offerings pleasing to God. The principle of imitating Christ's sacrifice became the basis of Christian worship. Even if the difficulties and unfriendly circumstances due to the new normal conditions do not make the attitude of surrender and offerings pleasing to God fade. AbstrakPenelitian ini mengulas perspektif nabi Amos tentang ibadah dan implikasinya dalam ibadah new normal. Untuk memperoleh tujuan penelitian tersebut peneliti menggunakan metode kualitatif dengan kajian literatur. Hasil penelitian mengungkapkan bahwa: pertama, ibadah hendaknya menghindari kemeriahan, kemewahan, dan kemunafikan. Gereja dan umat Allah masa kini perlu menghindari ibadah yang menonjolkan kemeriahan dan kemewahan yang dapat menjauhkan diri dengan Allah, sebaliknya lebih mengutamakan kepedu-lian sosial dan ibadah sederhana yang berkenan di mata Tuhan. Kedua, ibadah hendaknya disertai sikap yang setia kepada Tuhan dan menjauhi perbuatan dosa. Dengan kesetiaan, kondisi apa pun, termasuk new normal sekarang ini, tidak menghalangi seseorang untuk melakukan ibadah pribadi maupun ibadah bersama, serta kesetiaan tidak membuat diri jauh dari tempat ibadah. Ketiga, ibadah hendaknya disertai keadilan, kebenaran, dan kekudusan. Ibadah yang diiringi perbuatan nyata akan keadilan dan kebenaran dalam interaksi sosial. Keempat, ibadah hendaknya disertai pengorbanan dan persembahan yang berkenan di hadapan Allah. Prinsip meneladani pengorbanan Kristus menjadi dasar ibadah-ibadah umat Kristen. Sekalipun kesulitan dan keadaan yang tidak bersahabat karena kondisi new normal, tidak membuat sikap pengorbanan dan persembahan yang berkenan kepada Tuhan menjadi pudar.